The Management of Football Education and Training Center in Salatiga Central Java - Marsudi, Imam; K.S., Soegiyanto (The Journal of Educational Development, 2016)
This study aimed at describing and explaining the management of the Football Education and Training in Salatiga Central Java, including the human resource management, financial management, and facility management. The descriptive qualitative method applied in this study includes observation, survey, and interview. The population and respondents of this study were the manager, the coaches, the players, and ex-coaches as well as alumni of the Education and Training Center. There were 22 athletes considered as the respondents for this research. They stayed in the dormitory of the Center. The results of this study show that the human resource management to organize the Center was determined by the National Education of the Republic of Indonesia through recruitment of government officers, while the recruitment of coaches was determined by the National Education Office of Central Java Province through the sports management officers in charge of the financial commitment.Â  Among the criteria for recruiting players are 170 cm tall, obtaining average score of minimal 6.0, possessing good quality of physiological posture and football technique, based on tests and assessment. This Education and Training Center which was funded by the State Budget has been managed on the basis of the procedures of managing the state budget. The fund from the central government has been properly spent for salary of the coaches, studentsâ allowance, accommodation, and the like. Dealing with the facility management, it could be stated that the facilities owned by the Football Education and Training Center in Salatiga Central Java, for instance the football field, have fulfilled the national as well as international standard. The Center also has such other facilities as weight training equipment, classrooms, training equipments like training boots, school boots, training costumes, school uniforms, bags, textbooks and stationery, and dormitory. The Center also has three buildings for the committee members, the coaches, and a mosque, a sports hall and an office as the headquarters of the Training Center. The conclusion is that the human resource, financial, and accommodation ofÂ  the Football Education and Training Center in Salatiga Central Java has been managed properly. The recommendation is that in order for young football players to improve their quality in playing football in the future, all football associations or Training Centers in Indonesia apply human resource, financial, and facility management the way the Football Education and Trading Center in Salatiga Central Java has done.